2023
DOI: 10.1101/2023.08.22.554315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prebiotic proanthocyanidins inhibit bile reflux-induced esophageal adenocarcinoma through reshaping the gut microbiome and esophageal metabolome

Katherine M. Weh,
Connor L. Howard,
Yun Zhang
et al.

Abstract: The gut and local esophageal microbiome progressively shift from healthy commensal bacteria to inflammatory-linked pathogenic bacteria in patients with gastroesophageal reflux disease, Barrett's esophagus and esophageal adenocarcinoma (EAC). However, mechanisms by which microbial communities and metabolites contribute to reflux-driven EAC remain incompletely understood and challenging to target. Herein, we utilized a rat reflux-induced EAC model to investigate targeting the gut microbiome-esophageal metabolome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 97 publications
2
8
0
Order By: Relevance
“…We recently reported that C-PACs, rich in cranberry polyphenols, significantly inhibited EAC in a rat model through mitigating reflux-induced bacterial, inflammatory and immune-implicated proteins and genes as well as reducing esophageal bile acids, but through unknown processes [20]. These observations combined with metabolic enrichment results supported the hypothesis that C-PACs potentiate reflux-induced changes in bacterial metabolites, amino acids, fatty acids, bile acids and the TCA cycle, raising the question of transporter involvement [20]. In this study, we first comprehensively characterized bile reflux-induced transporter alterations in a rat EAC model and investigated C-PACs' capacity to mitigate reflux-induced transporter dysregulation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported that C-PACs, rich in cranberry polyphenols, significantly inhibited EAC in a rat model through mitigating reflux-induced bacterial, inflammatory and immune-implicated proteins and genes as well as reducing esophageal bile acids, but through unknown processes [20]. These observations combined with metabolic enrichment results supported the hypothesis that C-PACs potentiate reflux-induced changes in bacterial metabolites, amino acids, fatty acids, bile acids and the TCA cycle, raising the question of transporter involvement [20]. In this study, we first comprehensively characterized bile reflux-induced transporter alterations in a rat EAC model and investigated C-PACs' capacity to mitigate reflux-induced transporter dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…A STRING protein interaction prediction was performed (Figure 2) using a list of 20 key transporters that are dysregulated in the same direction in both animal and human data, along with key proteins altered in the rat reflux-induced EAC model and mitigated by C-PACs, as previously described and evaluated herein (Figure 3) [20]. The protein interaction prediction revealed a complex connection within transporters and between other key proteins dysregulated or mutated in EAC.…”
Section: Transporter Dysregulation Observed In Human Esophageal Cance...mentioning
confidence: 94%
See 3 more Smart Citations